Criminology and public theology : on hope, mercy and restoration - MILLIE, ANDREW (Bristol University Press, 2021)
This timely and unique contribution brings together leading scholars from criminology and theology to challenge criminal justice orthodoxy. They question the dominance of retributive punishment, and consider alternatives which draw on Christian ideas of hope, mercy and restoration.